Implementasi Data Mining Dalam Menentukan Korelasi Antara Pelanggaran Sikap Siswa Di Lingkungan Sekolah Lanjutan Advent Purwodadi Menggunakan Algoritma Association Rule - Gomgom Yosua Balutaro Sihotang (TeIKa, 2021)
The student is a "student subject" in which human values ​​as individuals, who as social beings who have a moral identity, need to be developed to reach a level of a process to achieve ideal results and the criteria for life as a human being expected by the nation and state. This study allows researchers to find the correlation value between data violations among students of the Adventist Purwodadi High School. Violation data is calculated using the association rule method using the FP-Growth algorithm. Namely by combining violation data based on attributes, namely the types of violations committed. The results received will provide information on the correlation of the hidden violations of 2016-2020 students at the Purwodadi Adventist High School. This study found 27 association rules. The results obtained are expected to be able to assist schools in arranging their students to suit the vision and mission of the Purwodadi Adventist High School.